Analisis Pengaruh Profabilitas, Likuiditas, Leverage dan Kompleksitas terhadap Ketepatan Waktu Penyampaian Laporan Keuangan (Studi Kasus Perusahaan Properti yang Terdaftar Pada Bursa Efek Indonesia Tahun 2019-2023) - Teguh Imawan; Saras Supeno; Laila Rossana; Sania Ferika; Najatu Rohmah (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to analyze the effect of profitability, liquidity, leverage, and complexity on the timeliness of financial reporting among property companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. Timely reporting is a crucial indicator for delivering relevant and credible financial information to stakeholders. The study utilizes secondary data obtained from the IDX's official website and applies multiple linear regression analysis along with classical assumption tests. The results indicate that profitability, liquidity, leverage, and complexity each have a significant partial effect on financial reporting timeliness. Simultaneously, all four variables also have a significant combined influence. The adjusted R- square value of 71.4% indicates that these independent variables substantially explain variations in reporting timeliness. These findings highlight the importance of sound financial management and organizational efficiency in supporting compliance with timely financial reporting.